A field guide to Cape Cod : including Nantucket, Martha's Vineyard, Block Island & Eastern Long Island - Lynch, Patrick J., 1953- (Yale University Press, 2019)
A richly illustrated full-color guide to the unique plants, wildlife, and environments of Cape Cod and the other nearby "Outer Lands" This essential guidebook presents the most abundantly illustrated and fascinating account of the natural history of Cape Cod, its nearby islands, Block Island, the western coast of Rhode Island, and southeastern Long Island ever published. Exploring the ecology and most common plants and animals of the various regional environments-- beaches, dunes, salt marshes, heathlands, and coastal forests-- the book also encompasses marine mammals, sea turtles, and fish offshore. Lavishly illustrated with images, maps, and photographs, the guide introduces readers to more than six hundred species of plants and animals of the region, including major whale and seal species. The book also provides a concise guide to the ecological history of the "Outer Lands," the glacial geology of the region, and Cape Cod's major environmental challenges, from climate change and sea level rise to the loss of wild habitats due to development. For nature-loving local residents and visitors alike, this essential book will be a well-loved resource